2013
DOI: 10.1007/s11746-013-2346-5
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Quality Characteristics of Rendered Chicken Oil for Biodiesel Production

Abstract: Whole dead poultry birds obtained from commercial layer farms were assessed for fat in the whole carcass and then dry rendered in three different rendering regimens T 1 , T 2 and T 3 (temperature = 120, 130 and 140°C and shell pressure = 1, 2 and 3 kg/cm 2 respectively) and the effect on the yield and quality of the rendered chicken oil were studied. The overall fat percentage of the whole dead poultry carcass was 14.55 ± 0.17 % and the fat content of 'greaves' was 14.49 ± 0.38 %. In the dry batch rendering tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
3
1
0
Order By: Relevance
“…Compared to the results of Teixeira et al (), the unsaponifiable matter contents of beef tallow and chicken‐skin fat are similar (0.91–2.64 vs. 0.99). Abraham et al () reported a range of 1.18–1.94% for the unsaponifiable matter content of chicken fat, which was very close to the result of this study. Pearson correlation analysis of data showed that unsaponifiable matter content was positively correlated with fat yield.…”
Section: Resultssupporting
confidence: 91%
“…Compared to the results of Teixeira et al (), the unsaponifiable matter contents of beef tallow and chicken‐skin fat are similar (0.91–2.64 vs. 0.99). Abraham et al () reported a range of 1.18–1.94% for the unsaponifiable matter content of chicken fat, which was very close to the result of this study. Pearson correlation analysis of data showed that unsaponifiable matter content was positively correlated with fat yield.…”
Section: Resultssupporting
confidence: 91%
“…This assay shows that poultry meat possesses three times higher unsaponifiable matter than domestic chicken (Table 1) [38]. Our result is also supported by several research reports [37,41,42].…”
Section: Discussionsupporting
confidence: 90%
“…The yellow emulsion layer could contain semi-saponified raspberry lipids. High temperatures facilitated the NaHCO 3 -induced saponification [ 43 ], further improving the release of embedded ellagic acid molecules, which agreed with the findings that the ellagic acid yield was positively correlated with the extraction temperature ( Figure 3 B).…”
Section: Discussionsupporting
confidence: 82%
“…The SBAE method in this study utilized NaHCO 3 as the principal functional chemical, which may induce saponification of raspberry lipids and therefore improve the extraction performance. Clearly, saponification is greatly correlated with the temperature [ 43 ]. As shown by Figure 5 B,C, SB40 product exhibited a clear yellow emulsion layer between the aqueous and solid phases, which was rather thin or barely seen in the SB100 product or other SBAE products at 100 °C.…”
Section: Discussionmentioning
confidence: 99%